Wpływ treningu na sprawność ogólną i specjalną piłkarzy Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy i MLKS Włókniarza Okonek = The impact of training on the efficiency overall and special players Youth Sports Training Center in Bydgoszcz and MLKS - Marchwant, Przemysław; Cieślicka, Mirosława; Muszkieta, Radosław; Zukow, Walery; Iermakov, Sergii (Journal of Education, Health and Sport, 2015)
Marchwant Przemysław, Cieślicka Mirosława, Muszkieta Radosław, Zukow Walery, Iermakov Sergii. Wpływ treningu na sprawność ogólną i specjalną piłkarzy Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy i MLKS Włókniarza Okonek = The impact of training on the efficiency overall and special players Youth Sports Training Center in Bydgoszcz and MLKS Włókniarz Okonek. Journal of Education, Health and Sport. 2015;5(5):463-486. ISSN 2391-8306. DOI 10.5281/zenodo.18158 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A463-486 https://pbn.nauka.gov.pl/works/562651 http://dx.doi.org/10.5281/zenodo.18158 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2015. Revised 18.04.2015. Accepted: 24.05.2015. Wpływ treningu na sprawność ogólną i specjalną piłkarzy Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy i MLKS Włókniarza Okonek The impact of training on the efficiency overall and special players Youth Sports Training Center in Bydgoszcz and MLKS Włókniarz Okonek Przemysław Marchwant, Mirosława Cieślicka, Radosław Muszkieta, Walery Zukow, Sergii Iermakov IKF, WKFZIT, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: trening, sprawność ogólną i specjalną, piłkarzy. Keywords: training, efficiency overall and special, players. Abstrakt Piłka nożna jest jedną z najpopularniejszych gier zespołowych na świecie. Świadczy o tym nie tylko masa kibiców w wielu krajach, ale także liczba zawodowo i amatorko uprawiających ten sport ludzi. Gra w piłkę nożną jest niezwykłą i cieszącą wielu ludzi formą rekreacji ruchowej, którą można uprawiać na różnych typach podłoża (trawiastych, piaskowych, betonowych) przez zarówno dorosłych jak i młodzież i dzieci. Badania zostały przeprowadzone w lutym 2014 roku wśród 23 juniorów młodszych MLKS Włókniarza Okonek. Wszyscy badani urodzili się w roku 1998. Testowana grupa zawodników na co dzień trenuje pod okiem trenera. Chłopcy trenują od sezonu 2013/14 w lidze okręgowej. Dwa treningi w tygodniu odbywają się na orliku, natomiast jeden na stadionie miejskim. W Okresie zimowym drużyna ma do dyspozycji halę sportową i salę fitness. Jednostki treningowe realizowane są zwykle 3-4 razy w tygodniu od 90 - 120 minut, a w okresie przygotowawczym jednostki zwiększone są do 4-5 razy na tydzień. Klub organizuje w przeciągu okresu przygotowawczego turnieje, które mają na celu kształtowanie umiejętności młodych adeptów. Ośrodek Szkolenia Sportowego Młodzieży w Bydgoszczy. Badania zostały przeprowadzone w marcu 2014 roku wśród 23 zawodnikach OSSM w Bydgoszczy. Wszyscy badani urodzili się w roku 1998. Testowana grupa zawodników na co dzień trenuje pod okiem szkoleniowca trenera. Chłopcy trenują w lidze junior młodszy. Dwa treningi w tygodniu odbywają się na orliku, natomiast 3 na stadionie miejskim. W okresie zimowym drużyna ma do dyspozycji halę sportową. Jednostki treningowe realizowane są zwykle 4-5 razy w tygodniu od 70 - 90 minut, a w okresie przygotowawczym jednostki zwiększone są do 5 razy. Podsumowując wyniki testu sprawności ogólnej można stwierdzić, że juniorzy OSSM w Bydgoszczy posiadają lepsze zdolności motoryczne takie jak: szybkość, moc, zwinność; jednakże pod względem wytrzymałości okazali się gorsi od sowich rówieśników z MLKS Włókniarz Okonek. Jeżeli chodzi o wyniki testu sprawności specjalnej trzy z czterech prób zdominowała drużyna z MLKS Włókniarz Okonek. Zawodnicy tej drużyny wykazali się lepszą skutecznością wykonywania zadań ruchowych w takich próbach jak: żonglerka piłką, uderzenie piłki do celu, uderzenie piłki na odległość. Pod względem budowy somatycznej badania wykazały, że wyżsi od zawodników OSSM w Bydgoszczy są zawodnicy MLKS Włókniarz Okonek o 1 cm. Co do masy ciała badanych zawodników jest podobnie zawodnicy OSSM w Bydgoszczy ważą mniej od swoich rówieśników z MLKS Włókniarza Okonek o 4 kg. W wynikach badań BMI obie drużyny wypadły rewelacyjnie. W drużynie OSSM Bydgoszcz 22 osób mieści się w przedziale wskazującym prawidłową masę ciała, jedna ma nadwagę. W drużynie MLKS Włókniarz Okonek 20 osób mieści się w przedziale wskazującym prawidłową masę ciała, jedna ma nadwagę, zaś dwie są otyłe. Słuszność drugiej hipotezy potwierdza się prawidłowy wskaźnik BMI ma większa ilość juniorów z OSSM w Bydgoszczy. Abstract Football is one of the most popular sports in the world. This is evidenced not only the mass of fans in many countries, but also the number of professionals and amatory people practicing this sport. The game of football is amazing and many people enjoying a form of recreation that can be grown on different types of substrates (grasslands, sand, concrete) by both adults and youth and children. The study was carried out in February 2014 years of 23 juniors MLKS Włókniarz Okonek. All subjects were born in 1998. A test group of players every day he trains under the tutelage of coach. The boys train from season 2013/14 in the district league. Two workouts per week are held on Orlik, while the one at the municipal stadium. In the winter time the team has at its disposal a sports hall and a fitness room. Training units are usually performed 3-4 times a week from 90 - 120 minutes, and during the preparatory units are increased to 4-5 times a week. The club organizes within the pre-season tournaments, which are aimed at developing skills for young students. Youth Sports Training Centre in Bydgoszcz. The study was conducted in March 2014 year among 23 players OSSM in Bydgoszcz. All subjects were born in 1998. A test group of players every day he trains under the tutelage of trainer trainer. The boys train young junior league. Two workouts per week are held on Orlik, while 3 at the municipal stadium. In the winter the team has at its disposal a sports hall. Training units are usually performed 4-5 times a week from 70 - 90 minutes, and during the preparatory units are increased to 5 times. Summarizing the results of the test overall efficiency it can be said that juniors OSSM in Bydgoszcz have better motor skills such as speed, power, agility; However, in terms of strength they turned out to be worse than the owl peers from MLKS Włókniarz Okonek. When it comes to special fitness test results three of four attempts to dominate the team with MLKS Włókniarz Okonek. Players of the team showed a better performance perform motor tasks in such trials as juggling the ball, hit the ball into goal, hitting balls at a distance. In terms of construction somatic studies have shown that taller than OSSM in Bydgoszcz players are the players MLKS Włókniarz Okonek about 1 cm. As for the weight surveyed players it is similarly OSSM players in Bydgoszcz weigh less than their peers in the MLKS Włókniarz Okonek about 4 kilograms. The BMI test results between the teams came out great. The team OSSM Bydgoszcz 22 people in the range indicating normal weight, overweight one. The team MLKS Włókniarz Okonek 20 people is in the range indicating normal weight, one is overweight, and the two are obese. The validity of the second hypothesis is confirmed normal BMI is greater than the number of juniors with OSSM in Bydgoszcz.